2022
DOI: 10.1007/s00117-022-01033-3
|View full text |Cite
|
Sign up to set email alerts
|

Endovaskuläre Aortenreparatur bei Endoleaks

Abstract: ZusammenfassungSämtliche Patienten nach endovaskulärer Versorgung eines Aortenaneurysmas bedürfen einer regelmäßigen Nachkontrolle, zumeist in jährlichem Abstand. Der kontrastmittelverstärkte Ultraschall und die Computertomographie-Angiographie (CTA) sind die wichtigsten diagnostischen Modalitäten für die Erkennung von Endoleaks. Die (CTA) erlaubt eine bessere Unterscheidung der verschiedenen Endoleak-Typen. Sogenannte Hochdruck-Endoleaks (Typ I und Typ III) stellen, wenn sich nicht kurzzeitig ein Spontanversc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…11 According to early-and mid-term complication rates, these rates are comparable to those of other stent grafts with suprarenal fixation. [14][15][16] Recently, Gennai et al reported their experience on outcomes, and risk factors of TIIIELs after EVAR. They analyzed 2565 EVAR cases over 26 years and 95 (3.7%) TIIIELs were diagnosed at a median interval of 49.5 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 According to early-and mid-term complication rates, these rates are comparable to those of other stent grafts with suprarenal fixation. [14][15][16] Recently, Gennai et al reported their experience on outcomes, and risk factors of TIIIELs after EVAR. They analyzed 2565 EVAR cases over 26 years and 95 (3.7%) TIIIELs were diagnosed at a median interval of 49.5 months.…”
Section: Discussionmentioning
confidence: 99%
“… 11 According to early- and mid-term complication rates, these rates are comparable to those of other stent grafts with suprarenal fixation. 14 16 …”
Section: Discussionmentioning
confidence: 99%